Cross-border territorial cooperation between France and Germany: Evolution, convergence and perspectives - Jean Peyrony; Franziska Sielker; Thomas Perrin (Cities and metropolises in France and Germany, 2022)
Over the past thirty years, new forms and mechanisms of governance have multiplied in the border regions of Europe. The French-German border has seemed to distinguish itself as an early adopter of new cooperation frameworks, often instigated by developments on the European level on the one hand and by bilateral national cooperation on the other hand. This paper delivers an analysis of French and German policies for territorial cooperation, and of the evolution of cross-border cooperation between the two countries. Taking the example of the Greater Region and the UpperRhine Region, we scrutinise two different representations of cross-border institutionalisation in-depth. We then discuss the renewed prospects for border regions stemming from the bilateral French-German Aachen Treaty. Following this analysis, we make use of three conceptual lenses - multi-level governance, soft spaces and inter-territoriality - to reflect on the evolution of territorial cooperation across this border. In conclusion, our reflections on the French-German situation inspire recommendations for a next phase in the development of European cross-border cooperation.
urn:nbn:de:0156-1119101; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Cross-border cooperation; France; Germany; Treaty of Aachen; soft spaces; inter-territoriality; multi-level governance